TiO2 DISPERSION TO IN SiO2-MONTMORILLONIT: EFFECT OF PRECURSOR TYPE - Is Fatimah (Jurnal Penelitian Saintek, 2009)
Dispersion of titanium dioxide into montmorilonite pillared silica (SiO2-montmorillonite) was performed in order to gain homogeneous dispersion of TiO2 in solid support having high specific surface area, thermal stability and chemical stability. In this research, effect of titanium precursor to the physicochemical character of material was studied. Three different precursors : TiCl4, TiOCl2 and  titanium tetraisopropoxide (TTIP) were dispersed on SiO2-montmorillonite  at the concentration of 5% followed by calcination at 400oC for 3 h. Evaluation on material character was studied based on XRD, surface area analyzer and spectrophotometer Diffuse Reflectance UV-Visible (DRUV-Vis) measurements.Result of research show that there is a strong dependency between material properties and tittanium precursor.  By three kind of precursors, it can be concluded that main factor playing  role in determination of dispersion homogeneity is pH of the system in that TiCl4 cause structure delamination of SiO2-montmorillonite. Based on physicochemical characters, it can remarkably concluded that the success of dispersion by variation of titanium precursors as follow: TTIPTiOCl2TiCl4 .